2023
DOI: 10.1039/d3np00002h
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic vulnerabilities of cancer stem cells and effects of natural products

Abstract: Residual tumor burden and chemotherapy-resistance point to a need for drug leads active toward cancer stem cells. Just as natural products have led the way for current treatments, the potential for novel applications of these molecules remains high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 367 publications
(543 reference statements)
0
1
0
Order By: Relevance
“…In 2023, Zhang et al showed that another harmine derivative effectively blocked TNBC growth and metastasis in mice, including the regulation of CSCs [138]. A more extensive review of natural products capable of regulating CSCs was recently published by Reisenauer et al [139]. Incidentally, harmine was also used to reduce TWIST1 activity in the model of ulcerative colitis described in the previous section [53].…”
Section: Drugs Targeting Emtmentioning
confidence: 99%
“…In 2023, Zhang et al showed that another harmine derivative effectively blocked TNBC growth and metastasis in mice, including the regulation of CSCs [138]. A more extensive review of natural products capable of regulating CSCs was recently published by Reisenauer et al [139]. Incidentally, harmine was also used to reduce TWIST1 activity in the model of ulcerative colitis described in the previous section [53].…”
Section: Drugs Targeting Emtmentioning
confidence: 99%